Conceptual model of the Tatun geothermal system, Taiwan. (July 2018) - Dobson, Patrick; Gasperikova, Erika; Spycher, Nicolas; Lindsey, Nathaniel J.; Guo, Tai Rong; Chen, Wen Shan; Liu, Chih Hsi; Wang, Chun-Jao; Chen, Shyh-Nan; Fowler, Andrew P.G.
Highlights: Developed updated conceptual model of the Tatun geothermal system. Zone C located on NE margins of system, based on temperature gradient and MT data. Exploration drilling needed to determine if near-neutral fluids are present. Abstract: The Tatun geothermal system, located in northern Taiwan, is hosted by the Plio-Pleistocene Tatun volcanic group, consisting dominantly of andesitic lavas, domes and pyroclastic flows. During the late 1960s and early 1970s, geologic mapping, geochemical sampling, geophysical surveys, and the drilling of numerous exploration and temperature gradient wells were conducted at Tatun under the leadership of the Mineral Research and Service Organization (MRSO), the predecessor to the geothermal group at the Industrial Technology Research Institute (ITRI). Deep (1–2 km) wells encountered commercial temperatures (200–300 °C) in the Matsao area, but these initial exploration efforts were discouraged by the presence of very acidic (pH <3.5) and highly corrosive fluids. Numerous geoscience studies conducted over the past 15 years at Tatun have shown that the central portion of the system is dominated by corrosive volcanic fluids, as evidenced by abundant SO2 as well as HCl. More reduced gases are encountered on the flanks of the system, suggesting that water-rock interaction may have at least partly neutralized the volcanic-derived fluids on the margins of this geothermal system. Scientists from Lawrence Berkeley National Laboratory (LBNL) and ITRI have been working together to develop an updated evaluation of the Tatun geothermal system, with the goal of evaluating the geothermal resource potential of the NE margins of the Tatun geothermal system (Zone C), just outside of Yangmingshan National Park. This study provides a review and analysis of existing and new fluid geochemistry data, describes new magnetotelluric data and associated 3-D modeling conducted at LBNL, and incorporates these data and analyses with information from previous studies to create an updated conceptual model for the Tatun geothermal system, with a focus on the Zone C region. These data all suggest that the Zone C area is located on the margin of the main Tatun geothermal system. An exploration well drilled by ITRI will provide important constraints regarding the thermal regime and fluid compositions for this marginal portion of the system.